Development of E-Module STEM integrated Ethnoscience to Increase 21st Century Skills - Zakiyah, Nikmatul Azmi; Sudarmin, Sudarmin (International Journal of Active Learning, 2022)
Education is the most important thing in preparing quality young people in the 21st century. The results of the analysis of learning in several secondary schools show that there are still several obstacles in the learning process, including the limited learning resources of students who only use the 2013 curriculum BSE books and have not approached the Ethno-STEM . This study aims to develop an E-Module with an Ethno-STEM Approach on Traditional Musical Instruments with Vibration, Waves, and Sound Materials to develop students' 21st century skills. This study uses a development research method (RD) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research data were taken using a questionnaire and test method. This development research resulted in an e-module with the characteristics of integrating the STEM approach with ethnoscience and the development of 21st century skills of students which include critical thinking skills, creative thinking skills, collaboration skills, and communication skills and equipped with evaluation questions containing ethnoscience. The results of the e-module validation assessment showed that it was very feasible with an average percentage of 87.75% and received a very good response from students with a percentage of 82.9%. The developed e-module is very effectively used as an additional learning resource for students with an effectiveness score of 83.72.